Exploring the effects of local air pollution on popliteal artery aneurysms - Leinweber, Maria-E.; Meisenbacher, Katrin; Schmandra, Thomas; Karl, Thomas; Torsello, Giovanni; Walensi, Mikolaj; Geisbuesch, Phillip; Schmitz-Rixen, Thomas; Jung, Georg; Hofmann, Amun Georg (Journal of Clinical Medicine, 2024)
Objectives: A growing body of evidence highlights the effects of air pollution on chronic and acute cardiovascular diseases, such as associations between PM10 and several cardiovascular events. However, evidence of the impact of fine air pollutants on the development and progression of peripheral arterial aneurysms is not available. Methods: Data were obtained from the multicenter PAA outcome registry POPART and the German Environment Agency. Means of the mean daily concentration of PM10, PM2.5, NO2, and O3 concentrations were calculated for 2, 10, and 3650 days prior to surgery for each patient. Additionally, weighted ten-year averages were analyzed. Correlation was assessed by calculating Pearson correlation coefficients, and regression analyses were conducted as multiple linear or multiple logistic regression, depending on the dependent variable. Results: For 1193 patients from the POPART registry, paired air pollution data were available. Most patients were male (95.6%) and received open surgical repair (89.9%). On a regional level, the arithmetic means of the daily means of PM10 between 2000 and 2022 were neither associated with average diameters nor runoff vessels. Negative correlations for mean PAA diameter and mean NO2, as well as a positive correlation with mean O3, were found; however, they were not statistically significant. On patient level, no evidence for an association of mean PM10 exposure over ten years prior to inclusion in the registry and PAA diameter or the number of runoff vessels was found. Weighted PM10, NO2, and O3 exposure over ten years also did not result in significant associations with aneurysm diameter or runoff vessels. Short-term air pollutant concentrations were not associated with symptomatic PAAs or with perioperative complications. Conclusions: We found no indication that long-term air pollutant concentrations are associated with PAA size or severity, neither on a regional nor individual level. Additionally, short-term air pollution showed no association with clinical presentation or treatment outcomes.